The tobacco‐using periodontal patient: role of the dental practitioner in tobacco cessation and periodontal disease management. Issue 1 (4th April 2016) - Chaffee, Benjamin W.; Couch, Elizabeth T.; Ryder, Mark I.
Abstract: Although the prevalence of tobacco use has declined in some parts of the world, tobacco use remains a persistent and, in some cases, growing problem that will continue to be a fundamental challenge facing dental practitioners in the decades ahead. Dental practitioners have a unique opportunity and professional obligation to be a positive influence in reducing the economic and social burden inflicted by tobacco use on dental and general health. In this article, the current noninvasive, evidence‐based approaches are presented for dental practitioners to help patients avoid initiating tobacco use, to encourage and assist patients in ceasing tobacco use and to address tobacco‐induced damage to periodontal supporting tissues.